Mechanisms of the negative potential associated with Leão’s spreading depolarization: A history of brain electrogenesis - Herreras, Oscar (J Cereb Blood Flow Metab, 2020)
Spreading depolarization (SD) is a self-propagated wave that provokes transient disorder of numerous cell and tissue functions, and that may kill neurons in metabolically compromised tissue. We examined the mechanisms underlying the main hallmark of SD, a giant extracellular potential (ΔV(o)) for which multiple electromotive forces have been proposed. The end-point is that neurons and not glia, dendritic channels and not spatial currents, and increased sodium conductance rather than potassium gradients, appear to be the main actors in the generation of the negative ΔV(o). Neuronal currents are established by two mechanisms, a voltage independent dendritic current, and the differential polarization along the neuron membranes. Notably, despite of a marked drop of ion gradients, these evolve significantly during SD, and yet the membrane potential remains clamped at zero no matter how much inward current is present. There may be substantial inward current or none in function of the evolving portion of the neuron dendrites with SD-activated channels. We propose that the ΔV(o) promotes swelling-induced dendritic damage. Understanding SD electrogenesis requires all elements relevant for membrane potential, action currents, field potentials and volume conduction to be jointly considered, and it has already encouraged the search for new targets to limit SD-related pathology.